Rhacocleis parnassica sp.nov. a new cryptic bush-cricket (katydid) species from Greece (Orthoptera: Tettigoniidae: Tettigoniinae) - Willemse, Luc; Odé, Baudewijn; Stefanidis, Apostolis (Zootaxa, 2025)
A new species of Rhacocleis, R. parnassica sp.nov. is described. We discovered the species on scree slopes at 1450 m on Mt. Parnassos, central Greece. This bush-cricket is morphologically distinct from all congeners, particularly in male cercal and titillator structures, and differs bioacoustically from closely related taxa. Although superficially resembling the scree-dwelling R. crypta and R. lithoscirtetes, it shows greater morphological affinity with R. distinguenda and R. werneri, and acoustic similarity with R. germanica and R. annulata. The species is currently known only from its type locality within the Natura 2000 site GR2450005. Its restricted range and potential exposure to wildfire and human disturbance highlight the need for further ecological research and conservation assessments. This discovery increases the number of Rhacocleis species in Greece to 17, underscoring the country’s exceptional Orthoptera diversity and the potential for additional undescribed taxa in poorly explored environments.